Factors Influencing Candidates’ Performance in English Language and Mathematics at West African Senior School Certificate Examination - Oluwatomi Modupeola Alade; Olaotan Oladele Kuku; Adunola Osoba (International Journal of Evaluation and Research in Education (IJERE), 2017)
The study investigated influence of some factors on the performance of selected West African Senior School Certificate Examination (WASSCE) candidates. It also examined the relationship between these factors and candidates’ performance. Factors investigated include socio-economic background of the candidates (SEB), study hours (SH), attitude towards English Language (ATTENG) and attitude towards Mathematics (ATTMAT). Secondary schools in Lagos State were divided into private and public secondary schools. Simple random sampling was used to select five out of the six educational districts in Lagos State. Then one public and one private secondary schools were selected in each of the five educational districts earlier selected in stage one. Thereafter, 30 senior secondary school III students were selected in each of the ten schools (5 public and 5 private schools). A total of 600 candidates (consisting of male and female participants) were expected, however, only 564 participants with complete data were found suitable for the study. An instrument tagged “Candidates Rating Scale (CRS)” was developed and used to measure their SEB, SH, ATTENG and ATTMA which were the independent variables while candidates’ scores at WASSCE was used as the dependent variable. Obtained data were analyzed by using multiple regressions. The results of the study indicate that there exists a positive correlation between WASSCE grades and all the variables in Mathematics but correlate with socio economic background only for English language.